Multifocal pulmonary mucinous cystic neoplasm with ovarian type stroma, a new finding in an extremely rare case report - Bita Geramizadeh; Bijan Ziyaian; Shima Khaleghi (Wolters Kluwer Medknow Publications, 2014)
Primary pulmonary mucinous cystic neoplasm is a rare tumor and there are only a few case reports in the English literature. Herein we report a very unusual multifocal pulmonary mucinous neoplasm. Microscopic sections revealed ovarian type stroma which was diffusely positive for estrogen receptor, same as its pancreaticobiliary counterpart. To the best of our knowledge such a presentation of pulmonary mucinous neoplasm has not been previously reported in the English literature.